Produção de repolho em função da idade das mudas - Magro, Felipe Oliveira [UNESP]; Salata, Ariane da Cunha [UNESP]; Bertolini, Erick Vinicius [UNESP]; Cardoso, Antonio Ismael Inacio [UNESP] (Universidade Federal de Roraima, 2011)
The seedling transplanting ages is a factor of great importance because it can affect the quality and yield of plants if the volume of the cell is not compatible with the phenology of seedlings at time of transplantation. The experiment was conducted at São Manuel Experimental farm, Faculdade de Ciências Agronômicas da UNESP, from March to August, 2009. The objective of this study was to evaluate the effect of seedling age on cabbage production, hybrid Kenzan. The seedlings were grown in polystyrene trays containing 128 cells. Seedings were done every four days and contained the following treatments: 37, 41, 45, 49 and 53 days after sowing (DAS). The experimental design was randomized blocks, with five replications. On transplantation’s day (11/05/2009), the number of leaves, fresh and dry weight and height, were evaluated to the characterization of seedlings. It was observed that the seedling age had no influence on traits at harvest: number of leaves inside and outside of “head”, fresh weight of shoot and “head”, dry mass of shoot and “head” and length of “heart”.

A idade de transplante das mudas é um fator de grande importância, pois pode afetar a qualidade e a produtividade das plantas se o volume da célula não for compatível às condições fenológicas das mudas no momento do transplante. O experimento foi conduzido na Fazenda Experimental São Manuel, pertencente à Faculdade de Ciências Agronômicas da UNESP, no período de março a agosto de 2009. O objetivo deste trabalho foi avaliar o efeito da idade das mudas na produção de repolho, híbrido Kenzan. As mudas foram produzidas em bandejas de poliestireno expandido contendo 128 células, sendo que as semeaduras foram realizadas a cada quatro dias compondo os seguintes tratamentos: 37, 41, 45, 49 e 53 dias após a semeadura (DAS). O delineamento experimental foi em blocos ao acaso, com cinco repetições. Foram avaliados, no dia do transplante (11/05/2009), o número de folhas, altura, massa fresca e massa seca da parte aérea, para a caracterização das mudas. Observou-se que a idade das mudas não teve influência nas características avaliadas por ocasião da colheita: número de folhas internas e externas à “cabeça”, massa fresca da parte aérea e da “cabeça”, massa seca da parte aérea e da “cabeça” e comprimento do “coração”.
Cabbage production in function of seedling age
Keywords: Brassica oleracea var; Capitata; Seedling production; Sowing; Brassica oleracea var; Capitata; Produção de mudas; Semeadura